Measurement of Resistance, Porosity, and Water Contact Angle of Porous Transport Layers for Low-Temperature Electrolysis Technologies - Ouimet, Ryan J.; Young, James L.; Schuler, Tobias; Bender, Guido; Roberts, George M.; Ayers, Katherine E. (Frontiers in Energy Research, 2022)
The porous transport layer is an important component of low-temperature electrolysis devices, such as proton exchange membrane water electrolyzers or anion exchange membrane water electrolyzers. PTLs have significant influence on the cell performance as their bulk resistance can impact the ohmic re-sistance, their contact resistance can impact electrode performance, and their structure can impact the liquid flow to the cell, which could cause mass-transport losses. In order to improve cell performance, optimization of the PTL is critical. Standardized protocols should be utilized to adequately compare PTLs being developed from different institutions. This method will detail a standardized protocol for measuring the resistance of the PTL using a four-wire setup and will also detail a process for measuring the porosity and water contact angle of the PTL using capillary flow porometry.